2000
DOI: 10.1200/jco.2000.18.2.325
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Predict Chemotherapy-Induced Myelosuppression in Lymphoma Patients: Role of the Tumor Necrosis Factor Ligand-Receptor System

Abstract: This study indicates that in addition to the dose of chemotherapy and the administration of hematopoietic growth factors, poor performance status and high p75-R-TNF levels can predict the occurrence of chemotherapy-induced myelosuppression in lymphoma patients. This model may help in selecting patients for prophylactic growth factor administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 21 publications
5
40
1
2
Order By: Relevance
“…The reasons for poor toleration of chemotherapy among elderly HL patients might be at least partly attributable to circulating tumour necrosis factor (TNF). High TNF-levels predict myelosuppression in patients with lymphoma (26). High levels of TNF are also seen in patients with HL (27).…”
Section: Discussionmentioning
confidence: 85%
“…The reasons for poor toleration of chemotherapy among elderly HL patients might be at least partly attributable to circulating tumour necrosis factor (TNF). High TNF-levels predict myelosuppression in patients with lymphoma (26). High levels of TNF are also seen in patients with HL (27).…”
Section: Discussionmentioning
confidence: 85%
“…Studies reviewed in this article showed risk factors for CIN or leukopenia (Table 1), FN (Table 2), and RDI (Table 3) in patients with NHL [16][17][18][19][20][21][22], ESBC [22][23][24][25][26], and other malignancies [27][28][29]. In these studies, advanced age, female sex,…”
Section: Risk Factors For Cinmentioning
confidence: 87%
“…Possible explanations for this include the compromised marrow reserve present in most CLL patients when therapy is required or the excess plasma TNF-␣ levels noted in this disease, 36,37 both factors known to predispose to chemotherapy-induced cytopenias. 38 However, a preliminary report on low-grade NHL noted similar enhanced myelosuppression when these 2 agents were combined, suggesting a more complicated mechanism may exist that is currently not well understood. 39 It is notable, nonetheless, that this excess neutropenia during induction with the combination of rituximab and fludarabine did not predispose to an excess number of neutropenic fever episodes or life-threatening infections when compared either with the sequential arm in this trial or with the previous intergroup trial, which administered fludarabine alone.…”
Section: Discussionmentioning
confidence: 99%